(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
Identità religiose nei neo-nazionalismi. Ebraismo e Sionismo: da identità religiosa a identità politica ABSTRACT: This article compellingly explores the pivotal role of Zionism, tracing its journey from the early religious motivations of Puritan Protestants to the emergence of both political and religious ideologies that catalyzed the establishment of a Jewish homeland. First manifesting during the British Mandate in Palestine, this movement gained further momentum with the formation of the State of Israel, a crucial outcome of the UN Resolution 181. Moreover, the article examines the profound consequences of the 1967 War and the ongoing occupation of Palestinian territories, highlighting the varied responses from the United Nations. It delves into the foundational narratives of Israel, revealing a transformation from an ethnic identity to an ethno-religious nationalism, and underscores the significant role of Judaism in this evolution, along with its legal ramifications. Finally, this analysis confronts the pressing social and intellectual challenges that arise from post-Zionism, addresses critiques of the movement, and discusses the emergence and radicalization of neo-Zionism, making a strong case for understanding these complex, ambiguous, and paradoxical dynamics in today’s context. SUMMARY: 1. Earlier English Puritan proto-Zionists and the role of Evangelical Zionism - 2. From the First Aliyah to secular and religious Jewish Zionism - 3. The ambiguous role of the British Empire from 1915 to 1947, the rise of political Zionism, and the increasing clashes between Jews and Arabs during the Mandate in Palestine - 4. The United Nations and the consequences of the UNSCOP Report: the Resolution 181 - 5. The Occupied Territories by Israel after 1967, illegal settlements, and the UN response - 6. Religious and political foundational narratives, from ethnic identity to ethno-religious nationalism and the legal consequences in the State of Israel - 7. Intellectual and social challenges of post-Zionism - 8. The rise of religious Zionism and the radicalization of neo-Zionism.